Effects of resistance exercise in the cardiac remodeling of myocardial infarction rats. (3rd October 2022) - Rodrigues, E; Souza, L M; Pontes, T H D; Gomes, M J; Pagan, L U; Murata, G M; Damatto, F C; Rego, A B G C; Lima, A R R; Reyes, D R A; Zornoff, L A M; Okoshi, K; et al.
Abstract: Introduction: Exercise is an important therapeutic strategy for heart failure (HF). However, the myocardial effects of resistance exercise during HF are not completely understood. In this study, we investigated the influence of resistance exercise on cardiac remodeling and molecular myocardial changes of rats with myocardial infarction (MI)-induced HF. Methods: Three months after MI induction or simulated surgery, Wistar rats were divided into three groups: Sham (n=14); MI (n=9); and MI subjected to resistance exercise (MI-R, n=13). Exercised rats trained 3 times a week during 12 weeks performing four climbs in a ladder with progressive loads. Cardiac structure and left ventricular function were assessed by echocardiogram. Myocyte diameters were measured in histological sections. Energy metabolism, lipid hydroperoxide, antioxidant enzymes activity, malondialdehyde, and protein carbonylation were evaluated by spectrophotometry. NADPH oxidase subunits (Nox2, Nox4, p22phox and p47phox) gene expression was assessed by RT-PCR. Statistical analysis: ANOVA and Tukey test or Dunn's test. Results: Mortality did not differ between MI-R and MI groups. MI-R and MI presented dilated left atrium and left ventricle with systolic and diastolic dysfunction. Exercise improved maximum carrying load with no changes in cardiac structure or left ventricle function. Myocyte diameter was lower in MI than Sham and MI-R. Lactate dehydrogenase and creatine kinase activities were lower in MI than Sham. Activity of citrate synthase and catalase was lower in MI and MI-R than Sham. Lipid hydroperoxide concentration was lower in MI-R than MI. Nox2 and p22phox gene expression was higher in MI-R than Sham. Gene expression of Nox4 was higher in both infarcted groups and gene expression of p47phox was lower in MI than Sham. Conclusion: Resistance exercise is safe and well tolerated by infarcted rats. Exercise increases maximum carrying load and reduces myocardial oxidative stress with no changes in cardiac structure or left ventricle function of infarcted rats. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): CNPq - National Council for Scientific and Technological Development